Cloning and Expression of the Organophosphate Pesticide-Degrading α-β Hydrolase Gene in Plasmid pMK-07 to Confer Cross-Resistance to Antibiotics. (16th May 2018) - Rangasamy, Kirubakaran; Athiappan, Murugan; Devarajan, Natarajan; Parray, Javid A.; Shameem, Nowsheen; Aruljothi, K. N.; Hashem, Abeer; Alqarawi, Abdulaziz A.; Abd_Allah, Elsayed Fathi
Abstract : Pesticide residual persistence in agriculture soil selectively increases the pesticide-degrading population and transfers the pesticide-degrading gene to other populations, leading to cross-resistance to a wide range of antibiotics. The enzymes that degrade pesticides can also catabolize the antibiotics by inducing changes in the gene or protein structure through induced mutations. The present work focuses on the pesticide-degrading bacteria isolated from an agricultural field that develop cross-resistance to antibiotics. This cross-resistance is developed through catabolic gene clusters present in an extrachromosomal plasmid. A larger plasmid (236.7 Kbp) isolated from Bacillus sp. was sequenced by next-generation sequencing, and important features such as α - β hydrolase, DNA topoisomerase, DNA polymerase III subunit beta, reverse transcriptase, plasmid replication rep X, recombination U, transposase, and S-formylglutathione hydrolase were found in this plasmid. Among these, the α - β hydrolase enzyme is known for the degradation of organophosphate pesticides. The cloning and expression of the α - β hydrolase gene imply nonspecific cleavage of antibiotics through a cross-resistance phenomenon in the host. The docking of α - β hydrolase with a spectrum of antibiotics showed a high G-score against chloramphenicol (−3.793), streptomycin (−2.865), cefotaxime (−5.885), ampicillin (−4.316), and tetracycline (−3.972). This study concludes that continuous exposure to pesticide residues may lead to the emergence of multidrug-resistant strains among the wild microbial flora.